Hindu Society Perception of Catur Varṇa in Bali - Ida Bagus Subrahmaniam Saitya; Ida Bagus Putu Adnyana (Institut Hindu Dharma Negeri Denpasar, 2021)
The social life of the Hindu community in Bali cannot be separated from the ins and outs of work which then reflects the profession of the people who claim it. Professions in the social life of society will give birth to something called the professional group. This professional group will then have a social impact in the form of life strata in society. There is a separation between one profession and another, which then gives birth to a concept of ideas called the Catur Varṇa. In recent years there has been a widespread dualism of perspectives on the meaning of this Catur Varṇa concept. Some of them stated that this concept was a tradition passed down from generation to generation and there were also those who stated that this concept was an idea to organize the social life of Balinese people. The Catur Varṇa concept itself can be understood through literature which gives birth to a reality and facts. The concept of Catur Varṇa has been degraded due to the cognitive bias of the Balinese Hindu community in Bali in embodying the meaning of this concept. So that this concept does not give birth to social life that is more organized but instead creates a social problem that causes inequality in the body of community life. This inequality must be corrected immediately so that it does not become a tradition that has increasingly worsened the atmosphere of social life in Bali. Because today the concept of Catur Varṇa is consciously shifting meaning into a new concept that we have previously called the term Catur Wangsa.